Kajian tentang Penerapan Kaidah Fiqhiyyah al-'Adatu Muhakkamah dalam Berbagai Aspek Kehidupan - Desmuliati, Maria; Ramadhan, Mohd Fawwaz; Afriyandi, Mhd; Ridwan, Muannif; Nur, Syamsiah; Hidayanti, Sri (Indra Institute Research & Publication, 2025)
The fiqhiyah rule “al-'Adatu muhakkamah” (customs can be used as a source of law) is one of the important principles in Islamic law. This research aims to examine fiqhiyah rules related to customs and their application in community life. The method used is library research by collecting data from fiqh books, ushul fiqh books, journals, and related articles. The results show that customs can be accepted as a source of law if they meet certain conditions, such as not contradicting the nash (Al-Quran and Hadith), generally applicable, reasonable, and bring benefit. The application of this rule is found in various aspects of life, such as dress customs, marriage traditions, economic transactions, worship procedures, and local traditions. This study concludes that the rule of “al-'Adatu muhakkamah” shows the flexibility of Islamic law in accommodating the positive values of local culture, as long as it does not deviate from the basic principles of religion, emphasizing Islam as a religion of rahmatan lil 'alamin.